Meningkatkan Ekonomi Masyarakat dan Perlindungan Ekologis Pegunungan Meratus Melalui Agroforestry Kopi di Desa Batu Perahu - Nabawi, Ahmad; Hamid, Ismar; Irfan, Muhammad; Febrianty, Nur'Aulia; Hairida, Gusti; Roji, Fkah; Bahjah, Noor; Sari, Dini Puspita; Dani, Muhammad Anwaruddin; Syahputri, Arya Vernanda; Salsabila, Putri (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2025)
This community service program was implemented in Batu Perahu Village, Batang Alai Timur Sub-district, South Kalimantan, with the main objective of improving economic sustainability through the development of a coffee agroforestry system. This village, known as part of the Meratus Mountains, faces economic and infrastructure challenges, making it one of the underdeveloped villages in the region. Local communities, who have a close relationship with nature, have great potential in the management of their natural resources. Through a participatory approach, the program includes the planting of 1,000 Arabica coffee seedlings, which is expected to increase agricultural yields and community income. Initial activities included socialization to introduce the concept of agroforestry to the community, technical training on coffee cultivation, and distribution of coffee seedlings to 26 local farmers. The training was designed to improve knowledge and skills in managing coffee farms as well as how to market the harvest effectively. The program implementation method, which includes living in the village and interacting directly with the community, aims to build trust and active participation. By paying attention to sustainability aspects, it is expected that the program will not only increase coffee production, but also preserve the environment. The results of the program show an improvement in the community's capacity to manage coffee farms and an increase in the size of the plantation. Thus, coffee can become a superior commodity capable of increasing the economic value of Batu Perahu Village, providing new hope for the welfare of the local community.